Effective treatment with para-aminomethylbenzoic acid for chronic disseminated intravascular coagulation associated with aortic dissection. Issue 3 (April 2015) - Cui, Qingya; Wu, Tianqin; Chen, Haifei; Qin, Longmei; Yu, Ziqiang; Shen, Hongshi; Wang, Zhaoyue
Abstract : Chronic disseminated intravascular coagulation is a rare complication of aortic dissection. Surgical correction or low molecular weight heparin is treatment of choice, but for a severe bleeding problem due to excessive fibrinolysis, para-aminomethylbenzoic acid would be a simple and effective therapeutic approach.